Identification of Pyrrolizidine Alkaloids in Senecio Plants by Liquid Chromatography-Mass Spectrometry - An-Jing Lu; Yan-Liu Lu; Dao-Peng Tan; Lin Qin; Hua Ling; Chang-Hong Wang; Yu-Qi He (Journal of Analytical Methods in Chemistry)
Pyrrolizidine alkaloids (PAs) are considered as the major constituents that cause hepatoxicity in Senecio plants. PAs can be found in about 3%–5% of the world’s flowering plants. Nowadays, the identification method of PAs by separation and preparation was too slow and lacked effective power. A rapid method to identify PAs in plants must be developed. Based on the fragmentation regularity, the hepatoxic PAs and nonhepatoxic PAs were characterized by liquid chromatography-mass spectrometry (LC-MS). The detailed structures of PAs in five Senecio plants were identified based on tandem mass spectrometry (MS/MS) spectrum and chemical research information. In the present study, some new fragmentation regularities of PAs have been found, such as product ions at m/z 122, m/z 140 and m/z 124, m/z 142, which have been discovered as the characteristic fragments of lactone and mono-esterase type of saturated PAs, respectively. Moreover, two product ions at m/z 120 and m/z 138 have been reported as the characteristic fragments of unsaturated PAs. Some of them were found in Senecio species for the first time, and some of them may be new nature product or even new compound. Finally, we classified these plants into five categories based on PAs which were identified in the present study; the result corresponded with the classification by morphology. In addition, we have found some constituents that have odd molecular weight number only in Senecio species but not in Ligularia species; the detailed structures of these non-PAs constituents need penetrating study. LC-MS was rapid and sensitive method for detecting and identifying PAs in plants. Pyrrolizidine alkaloids were the toxiferous constituent of Senecio plants. In this study, we found that PAs can be used as the characteristic constituent of Senecio species.